Debt to Equity Ratio, Sales Growth, Current Ratio and Working Capital Turnover on Financial Performance of Consumption Goods Industry Sector in Indonesia Stock Exchange in 2013-2018 - Axel Valim; Yeni Ariesa; Anthony; Zessi; Deo Mora Gratia; Indah Rahmanisa (Journal of Research in Business, Economics, and Education, 2020)
This study aims to prove whether the Debt Equity Ratio, sales growth, current ratio and working capital turnover are factors that affect the financial performance of companies in the consumer goods industry sector on the Indonesia Stock Exchange in 2013-2018. A population of 48 companies was searched using purposive sampling so that the sample amounted to 25 with a total of 150 data. Data analysis was tested by multiple regression which fulfilled classical assumptions. The conclusion of this study shows that partially there is no influence of the independent variables under study on company performance, but if simultaneously DER, sales growth, current ratio and working capital turnover have a significant effect on company performance.